The Correlation Between The Severity Of Acne Vulgaris And Quality Of Life Using The Cardiff Acne Disability Index (CADI) Questionnaire At Zaira Skin Care Main Clinic In Jambi City - Fairuza, Putri Azka; Sri Yusfinah Masfah Hanum; Mirna Marhami Iskandar; Fitriyanti; Ahmad Syauqy (Journal of Medical Studies, 2025)
ABSTRACT Background: Acne Vulgaris (AV) is a skin condition characterized by chronic inflammation. The degree of AV used in this study is based on the Lehmann criteria. The quality of life in this study was measured using the CADI questionnaire. The CADI questionnaire is used to assess quality of life specifically for individuals with Acne Vulgaris. Objective: To determine whether there is a relationship between the degree of AV and the quality of life of AV patients who seek treatment at Zaira Skin Care Clinic, Jambi City. Methods: Of the 97 respondents, 43 respondents (44.3%) had mild AV, with 23 respondents (23.7%) experiencing mild quality of life disturbances, 16 respondents (16.5%) experiencing severe quality of life disturbances, and 4 respondents (4.1%) experiencing very severe quality of life disturbances. In the moderate AV group, consisting of 45 respondents, 13 respondents (13.4%) had mild quality of life disturbances, 24 respondents (24.74%) had moderate disturbances, and 8 respondents (8.25%) had severe disturbances. In the severe AV group, consisting of 9 respondents, 2 respondents (2.06%) experienced moderate quality of life disturbances, and 7 respondents (7.22%) had severe disturbances. The data from the Kendall-tau test analysis showed a significant result with p = 0.001 (p < 0.05), and a correlation coefficient of 0.381. This indicates a positive and moderately significant relationship. Results: The data from the Kendall-tau test analysis showed a significant result with p = 0.001 (p < 0.05) and a correlation coefficient is 0.381. This indicates a positive and moderately significant relationship. Conclusion: There is a relationship between the degree of AV severity and the quality of life of AV patients. Keywords: Acne Vulgaris, AV severity, quality of life, CADI